2010
DOI: 10.1165/rcmb.2008-0362oc
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Alveolar Macrophages upon Instillation of Lipopolysaccharide in the Human Lung

Abstract: The airways are continuously exposed to respiratory pathogens, which may result in bacterial pneumonia, one of the most common infectious diseases and the leading cause of sepsis. Considering that recurrent exposure to microbial products can lead to tolerance of immune cells, and that this might contribute to the susceptibility to nosocomial infection, we investigated the effect of in vivo lipopolysaccharide (LPS) instillation on the responsiveness of alveolar macrophages. In eight healthy humans, sterile sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…FACS-sorted Aoah -/- lung epithelial cells also had higher KC mRNA expression than did Aoah +/+ epithelial cells (Fig 5H). It has been shown that, distinct from macrophages form other sites, AMs that have been exposed to LPS in vivo are resistant to endotoxin tolerance or even increase their innate responsiveness [3537]. To confirm that AMs maintain their responsiveness, 7 days after PBS or LPS instillation i.n., we explanted AMs and stimulated them with a low dose (100 pg/ml) of LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FACS-sorted Aoah -/- lung epithelial cells also had higher KC mRNA expression than did Aoah +/+ epithelial cells (Fig 5H). It has been shown that, distinct from macrophages form other sites, AMs that have been exposed to LPS in vivo are resistant to endotoxin tolerance or even increase their innate responsiveness [3537]. To confirm that AMs maintain their responsiveness, 7 days after PBS or LPS instillation i.n., we explanted AMs and stimulated them with a low dose (100 pg/ml) of LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct from peritoneal macrophages, however, upon exposure to LPS in vivo , AMs do not become tolerant [35,36]. Instead, they respond to repeated LPS exposure by maintaining or even increasing their responsiveness [37,48]; they are able to produce chemoattractants and cytokines in the presence of persistent LPS (Fig 5), thus delaying clearance of neutrophils and prolonging inflammation. For these cells (and presumably for other LPS-responsive cells that do not develop tolerance), MAMP inactivation is especially important to terminate inflammatory responses and prevent tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…The combined data demonstrate that constitutive TLR4 expression in freshly isolated primary human alveolar macrophages is low, but quickly and transiently upregulated at the gene and protein level by LPS in vitro. Inhalation of LPS by healthy humans decreases TLR4 mRNA expression in alveolar macrophages after 6 h, 59 whereas lung subsegmental instillation of LPS in healthy humans does not influence the cell surface expression of TLR4 or CD14 on alveolar macrophages recovered after the same time, 60 suggesting that LPS application procedures in humans differentially affect TLR4 abundancy in alveolar macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanism of clearance, at the alveolar surface, is via the activity of the alveolar macrophages (Forman et al, 1980(Forman et al, , 1982Hartmann et al, 1984;Stringer et al, 1995;Bates and Fisher, 1996;Kaul and Forman, 1996;Yagisawa et al, 1996;Tang et al, 2001;Iles et al, 2002;Jimenez et al, 2002;Quintero and Wright, 2002;Tao and Kobzik, 2002;Chin et al, 2003;Hjort et al, 2003;Laskin et al, 2003;Fakhrzadeh et al, 2004a,b;Rao et al, 2004;Kanj et al, 2005Kanj et al, , 2006Rothen-Rutishauser et al, 2005;Hu et al, 2006Hu et al, , 2007Sunil et al, 2007;Baker et al, 2008;Gaschler et al, 2008;Geiser et al, 2008;Manzer et al, 2008;Naito et al, 2008;Yamasaki et al, 2008;Jordan et al, 2009;Kuronuma et al, 2009;Pauluhn, 2009;Ryman-Rasmussen et al, 2009;Woodruff et al, 2009;Hoogerwerf et al, 2010;Snyder et al, 2010;Fuchimoto et al, 2011;Hristova et al, 2011;Poole et al, 2011;Groves et al, 2012;…”
Section: Inflammation In the Lungmentioning
confidence: 99%